Synthesis of guanidino analogues of PMPDAP and their immunobiological activity - Česnek, Michal; Holý, Antonín; Masojídková, Milena; Kmoníčková, Eva; Zídek, Zdeněk (Bioorganic & medicinal chemistry, 2008)
A series of novel 9-, 7- and 3-substituted 2- or 6-guanidinopurines as analogues of potent antiviral and immunobiologically active compound enantiomers of PMPDAP was synthesized and evaluated for their biological activity. Compounds containing the combination of guanidino and amino group at the purine moiety enhanced the interferon-gamma-triggered NO production in murine macrophages and stimulated the secretion of cytokines and chemokines in both murine macrophages and human peripheral blood mononuclear cells. The most active compounds are 27 and 54. None of the compounds tested exhibited any significant cytostatic effect or antiviral effect.
Keywords: molekulární struktura; Adjuvants, Immunologic; Animals; organofosforové sloučeniny; Chemokines; Humans; Macrophages, Peritoneal; adjuvancia imunologická; Mice, Inbred C57BL; lidé; financování organizované; techniky kombinatorické chemie; zvířata; guanidiny; myši inbrední C57BL; Cytokines; Combinatorial Chemistry Techniques; peritoneální makrofágy; myši; chemokiny; adenin; Financing, Organized; Female; Stereoisomerism; Molecular Structure; cytokiny; oxid dusnatý; Organophosphorus Compounds; Mice; Guanidines; Adenine; ženské pohlaví; Nitric Oxide